Effect of antibacterial therapy on the clinical course of streptococcal tonsillopharyngitis in children. - T. Haiduk (Medičnì Perspektivi, 2019)
The aim of this study was to determine the effect of antibiotic therapy (AT) on the clinical course of streptococcal tonsillopharyngitis (STP) in children, depending on the timing of its administration, since the data on the need to start AT in the first days of the disease to achieve the effect are controversial. A retrospective analysis of inpatient medical records at “The Communal Dnipro City Clinical Hospital N 21 named after Professor Ye.G. Popkova” DRC” in the period from January 2012 to December 2018 was conducted. The inclusion criteria for the study were: 1) the diagnosis - tonsillopharyngitis; 2) the age of the patient: 3 to 18 yrs; 3) the exclusion of an alternative diagnosis (diphtheria, infectious mononucleosis, scarlet fever); 4) no complications; 5) positive results of the culture study on β-hemolytic streptococcus group A (GAS) (Streptococcus pyogenes) of the oropharyngeal swab. The study included 109 medical cards of children with STP. Depending on the timing of the onset of rational AT, all patients were divided into 5 groups. The first one consisted of 27 children who received AT from the 1st day of the disease, 2nd - 48 children (AT from the 2nd day), 3rd - 17 children (AT from the 3rd day) and the fourth - 7 children (AT from the 4th day), 5th - 10 children (AT from the 5th day). Clinical symptoms were evaluated by examining the patient with the main objective and subjective symptoms of STP. It was a retrospective open comparative study. All patients received the full recommended course of STP AT. The study showed no significant differences in the reduction of clinical symptoms of STP, regardless of the timing of antibiotic therapy (1-5 days from the onset of the disease) in almost half of patients with STP, which confirms the inadequacy of antibacterial therapy in children with tonsillopharyngitis. We believe that antibiotic therapy should only be used to prevent late complications in cases of children with tonsillopharyngitis only with a confirmed GAS etiology, and we propose the widespread use of the McIsaac Score, the Streptococcus Expression Test (RST) and the culture study of the oropharyngeal swab to confirm the etiology of GAS in children with tonsillopharyngitis to reduce the frequency of antibiotics overusing.